Peningkatan Kapasitas UMKM Bengkalis melalui Pelatihan Penghitungan Harga Pokok Produksi dan Penjualan - Ratnawati, Vince; Sari, Ria Nelly; Anugerah, Rita; Silfi, Alfiati; Hanif, Rheny Afriana (Jurnal Pengabdian kepada Masyarakat Politeknik Negeri Batam, 2025)
The main problems faced by the majority of micro, small, and medium enterprises are a lack of knowledge of systematic cost recording and an inability to determine the correct selling price. This community service activity aims to improve the understanding and skills of micro, small, and medium enterprises (MSMEs) in calculating the cost of production and the cost of goods sold in accordance with applicable regulations. The implementation method for this community service activity consists of a pre-test, delivery of materials through lectures, interactive dialogue, simulation of COGS calculation, and a post-test. The participants in this activity were 25 micro, small, and medium enterprises in Bengkalis Regency. The results of the activity showed a significant increase in participants' understanding, as reflected in the average pre-test score rising from 49.1 to 77.5 in the post-test. Participants understood the cost components that make up COGS, differentiated between direct and indirect costs, and applied COGS calculation methods for both trading and manufacturing businesses. Overall, this activity succeeded in increasing MSMEs' capacity to record costs and determine selling prices more accurately and professionally. It is hoped that this increased understanding will contribute to the development of more efficient, transparent, and sustainable businesses.